EXPRESSION, PURIFICATION AND BIOCHEMICAL CHARACTERIZATION OF RECOMBINANT PHOSPHOHYDROLASE APPA IN ESCHERICHIA COLI - Abeldenov, S.; Kirillov, S.; Nurmagambetova, A.; Kiribayeva, A.; Silayev, D.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2014)
Development of fodder and increase of feed efficiency is an urgent task for livestock and poultry in Kazakhstan. An important characteristic of feed is the content of bioavailable phosphorus. Traditional source of phosphorus in feed is the mineral phosphate. New and cost-effective way to improve the quality of feed is to mobilize bound phosphate from indigestible plant components. Development of pig and poultry production has increased the cost of traditional sources of organic phosphorus feed (fish and meat and bone meal). At the same time, the limitations of the world's reserves of phosphorus-containing minerals will lead to the progressive increase of the price of animal feed with mineral additives. Relatively new and cost-effective way to address the shortage of bioavailable phosphorus for livestock, poultry and fish farming is the use of feed additives - phytase. Phytase - a group of enzymes phosphohydrolases cleaving the ester bond in the molecule of phytic acid and releasing one or more residues of phosphoric acid. In this work gene appA of Escherichia coli BL21 (DE3) was cloned into plasmid vector under T7 promoter control and was expressed resulting in high purity recombinant phytase AppA. Optimal cultivation temperature and induction conditions, cell lysis conditions, purification conditions of recombinant enzyme AppA were determined. Phytase activity assay was performed for recombinant enzyme. Work has absolute novelty for the biotechnology industry in Kazakhstan.